Public acceptance on nanotechnology in edible food material: an empirical study from China - Liao, Zhenwei; Ali, Mohd Helmi; Tu, Dan; Xiong, Shanmei; Suleiman, Norhidayah (Universiti Putra Malaysia, 2025)
Nanotechnology in Edible Food Materials (NEFM) raises health concerns and public skepticism, necessitating enhanced regulatory scrutiny and public acceptance strategies. This study delves into the key factors influencing public acceptance of NEFM in China, offering vital insights for strategic policy development to promote NEFM integration. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), the study analyzed 275 validated responses from Chinese citizens. It reveals that epistemic trust, social trust, and self-efficacy play crucial roles in shaping public attitudes towards NEFM, each through distinct mechanisms. A notable finding is the inverse relationship between epistemic trust and NEFM acceptance, mediated by perceived risks and benefits. This highlights the intricate balance required to address potential negative consequences and uncertainties of NEFM. Public trust in governmental bodies emerges as a significant determinant of NEFM approval, affecting both risk and benefit perceptions, in contrast to the negligible impact of trust in commercial entities. This study also underscores the positive correlation between perceived benefits and NEFM acceptance, suggesting the importance of highlighting tangible NEFM benefits in consumer education and public outreach programs. The study contributes to the theoretical framework by integrating insights from the Social Cognitive Theory and the Theory of Planned Behavior. It provides a comprehensive understanding of factors fostering public acceptance of NEFM, vital for policymakers and stakeholders in developing strategies that enhance public perception and acceptance, thereby fostering the growth and advancement of NEFM in China and beyond.